1980
DOI: 10.1136/hrt.43.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of aortic stenosis by Doppler ultrasound.

Abstract: NorwaySUMMARY The peak pressure drop across the aortic valve in aortic stenosis has been measured by Doppler ultrasound. Maximum velocity in the Doppler signal from the aortic jet was recorded using a maximum frequency estimator. With an angle close to zero between ultrasound beam and maximal velocity in the jet, peak pressure drop can be calculated from the maximal velocity measured; a larger angle will underestimate maximal velocity and pressure drop.In 57 of 63 patients with aortic stenosis, the aortic jet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
1
2

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(141 citation statements)
references
References 6 publications
1
137
1
2
Order By: Relevance
“…Measurement of the exact timing between the pressure and velocity events would require precise calibration of the relative recording delays and chart speeds of the Doppler and catheterization systems, which was not done i \n this study. A small phase delay of velocity versus pressure is predicted on the basis of fluid dynamics calculations (Hatle et al, 1980).…”
Section: Quantitative Pressure Gradient Analysismentioning
confidence: 99%
“…Measurement of the exact timing between the pressure and velocity events would require precise calibration of the relative recording delays and chart speeds of the Doppler and catheterization systems, which was not done i \n this study. A small phase delay of velocity versus pressure is predicted on the basis of fluid dynamics calculations (Hatle et al, 1980).…”
Section: Quantitative Pressure Gradient Analysismentioning
confidence: 99%
“…a) RVSP calculated from a properly aligned Tricuspid regurgitation (TR) jet using modified Bernoulli's equation. 4,5,6 RVSP was calculated by adding the RA pressure (jugular venous pressure from the angle of LOUIS + 5 cms) to the TR gradient. b) dP/dT of TR jet (to assess the RV systolic function)-7,8,9,10 on the Doppler signal of TR jet two points were taken -one corresponding to a velocity of 1 m/sec (v1) and another to 3 m/sec (v2).…”
Section: Methodsmentioning
confidence: 99%
“…9) RV dysfunction predicts an impaired contractile reserve and decreased survival in patients with both moderate and advanced HF. 45,46) Di Salvo, et al 9) found that RVEF of less than 35% during exercise was the only independent predictor of event-free survival in a multivariate proportional hazards model in advanced HF. Cardiopulmonary exercise testing could help to better stratify the risk of CHF patients while not negatively affecting the prognosis.…”
Section: )mentioning
confidence: 99%